PENGARUH LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP KEPUASAN KERJA KARYAWAN PADA PT. INDOMARCO PRISMATAMA CABANG MEDAN - Sudrajat, Imam; Yuliana, Yayuk; Munawaroh, Munawaroh (UNIVERSITAS SARI MUTIARA INDONESIA, 2022)
This study aims to determine whether the variables of work environment and organizational culture affect the job satisfaction of employees of PT. Indomarco Prismatama. This study uses a quantitative descriptive method with data analysis techniques used, namely multiple linear regression and hypothesis testing (t-test and F-test). With a population of 358 respondents with a tolerance limit of 10% which is calculated by the Slovin formula, the number of samples obtained is 78 respondents by determining the sample using purposive sampling technique. Data collection techniques by distributing questionnaires. From the results of multiple analysis, the equation Y = 4.945 + 0.418X1 + 0.465X2 + e. The results of the partial test (t-test) showed that the work environment (X1) had a positive effect on job satisfaction of PT. Indomarco Prismatama, it can be seen from the value of t test (3.436) > t table (1.66543) with a significance of 0.001 < 0.05. Meanwhile for the organizational culture variable (X2), the results showed that organizational culture (X2) had a positive effect on job satisfaction of PT. Indomarco Prismatama, it can be seen from the value of t test (3.827) > t table (1.66543) with a significance of 0.000 <0.05. While the results of the simultaneous test (F-test) of the two independent variables on the dependent variable, the results show that together the work environment and organizational culture variables have a significant influence on employee job satisfaction at PT. Indomarco Prismatama, it can be seen from the value of f test (89.640) > ftabel (3.12) with a significant value of 0.000 <0.05. The value of the coefficient of determination reached 0.697, which means that the work environment and organizational culture variables affect employee job satisfaction at PT. Indomarco Prismatama by 69.7%. While the remaining 30.3% is influenced by other factors outside of this study.